Tracheo–bronchial adenoid cystic carcinoma: A retrospective study. Issue 4 (20th May 2019) - Ning, Ye; He, Wenxin; Bian, Dongliang; Xie, Dong; Jiang, Gening
Abstract: Objectives: Adenoid cystic carcinoma (ACC) of the trachea and bronchus is rare, representing 1% of all respiratory tract cancers. We presented our experiences in treating tracheal–bronchial ACC and the results of long‐term surveillance. Methods: We conducted a retrospective study of treating tracheo–bronchial ACC. From 2009 to 2014, 42 patients presented to our department. All of them received surgical resection and adjunctive therapy. Results: R0 resections were achieved in 33 patients, whereas 15 patients whose lesions spread outside the tracheo–bronchial lumens. Nine patients had R1 resections followed by radiation and chemotherapy. The 5 year survival rate of R1 resection group showed no difference compared to the R0 resection group, but the 5 year disease‐free survival rate showed difference in extra‐lumenal invasion (ELI) and non‐ELI group ( P  = 0.0357 < 0.05), although no difference was seen in the overall survival rate in these two groups. Conclusions: ACC of the trachea and bronchus is a rare and low‐to‐moderate grade malignant tumor. When the R0 resection is over risky or may cause mortal complication, the R1 resection with adjunctive therapy is acceptable for patients to obtain a promising prognosis, whereas pathological ELI is an adverse prognostic indicator.